Anti-tumor efficacy of a combination therapy with PD-L1 targeted alpha therapy and adoptive cell transfer of PD-1 deficient melanoma-specific human T-lymphocytes. (1st January 2021) - Marotte, L; Capitao, M; Deleine, C; Beauvais, T; Cadiou, G; Perrin, J.; Chérel, M; Scotet, E; Guilloux, Y; Bruchertseifer, F; Morgenstern, A; Jarry, A; et al.
ABSTRACT: The optimization of adoptive transfer approaches of anti-tumor T cells requires both the functional improvement of the injected T cells and the modulation of the tumor microenvironment, favoring the recruitment of these T cells and their activation. We have recently shown the therapeutic benefit of two approaches tested individually in a melanoma model wich were on one hand the adoptive transfer of specific T cells deficient for the expression of the inhibitory receptor PD-1, and on the other hand PD-L1 targeted alpha therapy (TAT). In this study, we sought to investigate the efficacy of these two therapies combined, compared to each monotherapy, in order to evaluate the synergy between these two approaches, in the same melanoma model. Here we used melanoma-specific T-cell clones, previously validated for the edition of PDCD1 gene and with previously demonstrated superior anti-tumor activity than their wild-type counterparts, after adoptive transfer in NSG mice engrafted with PD-L1 expressing human melanoma tumors. We also used a previously validated TAT approach, using a 213 Bi-anti-human-PD-L1 mAb, alone or in combination with adoptive cell transfer, in the same mouse model. We confirmed previous results obtained with each monotherapy and documented the safety and the superior ability of a combination between the adoptive transfer of PD-1 deficient T cells and TAT targeting PD-L1 to control the growth of melanoma tumors in NSG mice. This study provides the first proof-of-concept of the efficacy of a combination therapy using TAT, adoptive cell transfer and genomic editing of IC-coding genes.